Breakdown of the few-level approximation in dipole-dipole interacting systems - Kiffner, M; Evers, J; Keitel, C (2007)
The validity of the few-level approximation is investigated in a system of two dipole-dipole interacting four-level atoms. Each atom is modelled by two complete sets of angular momentum multiplets. We provide two independent arguments demonstrating that the few-level approximation in general leads to incorrect predictions if it is applied to the Zeeman subleveis of the atomic level scheme. First, we show that the artificial omission of subleveis generally leads to incorrect eigenenergies of the system. The second counterexample involves an external laser field and illustrates that the relevant states in each atom are not only determined by the laser field polarization, but also by the orientation of the atomic separation vector. As the physical origin of this outcome, we identify the dipole-dipole interaction between orthogonal dipole transitions of different atoms. Our interpretation enables us to identify conditions on the atomic level structure as well as special geometries in which (partial) few-level approximations are valid.